2014
DOI: 10.1111/ejn.12763
|View full text |Cite
|
Sign up to set email alerts
|

α‐Synuclein staging in the amygdala of a Parkinson's disease model: cell types involved

Abstract: Lewy bodies (ubiquitin and α-synuclein aggregates) can be detected in brain areas in a predictable sequence of six neuropathological stages in Parkinson's disease. Brainstem and olfactory structures are involved in stage 1, whereas the substantia nigra and amygdala are involved in stage 3, prior to cortical spreading. Amygdaloid pathology has been suggested to contribute to non-motor symptoms such as olfactory dysfunction and emotional impairment. This work analysed the distribution of α-synuclein at 16, 30, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 81 publications
(115 reference statements)
4
14
0
Order By: Relevance
“…We further demonstrated that CB expression decreased with age in all hippocampal regions of control mice, but only in the CA1 region of PD mice. Expression of CB was lower in general in PD mice, in agreement with previous findings in the amygdala . Deficits in CB are associated with impaired spatial learning and long‐term potentiation in mice, and CB overexpression appears to be neuroprotective against PD manifestations .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We further demonstrated that CB expression decreased with age in all hippocampal regions of control mice, but only in the CA1 region of PD mice. Expression of CB was lower in general in PD mice, in agreement with previous findings in the amygdala . Deficits in CB are associated with impaired spatial learning and long‐term potentiation in mice, and CB overexpression appears to be neuroprotective against PD manifestations .…”
Section: Discussionsupporting
confidence: 90%
“…This is sufficient for the development of α‐synuclein intracellular aggregates and motor deficits in these mice, similar to those observed in human PD patients . Aggregates of α‐synuclein initially develop in the olfactory bulb, olfactory cortex, and amygdala at 2 months of age and significantly increase at 8 months of age. This correlates with an onset of severe motor manifestations at 8‐9 months of age and deficits in spatial memory, in basal synaptic transmission, in paired‐pulse facilitation, and long‐term depression .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Though not many studies have investigated the α-synuclein levels in the amygdala, Flores-Cuadrado et al [23] showed that α-synuclein positive cells are present mostly in the basolateral and cortical amygdala in the A53T transgenic mice, which overexpress α-synuclein. They also showed that there were no increases in the number of α-synuclein positive neurons in the amygdala over 43 weeks between the transgenics and the controls.…”
Section: Discussionmentioning
confidence: 99%